2000
DOI: 10.1111/j.1151-2916.2000.tb01428.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hot‐Pressing Temperature on Densification and Mechanical Properties of Titanium Diboride with Silicon Nitride as a Sintering Aid

Abstract: The effect of hot-pressing temperature on the densification behavior and mechanical properties of titanium diboride (TiB 2 ) was investigated. TiB 2 specimens were hot-pressed for 1 h at temperatures in the range of 1500°-1800°C, with an addition of 2.5 wt% of silicon nitride (Si 3 N 4 ) as a sintering aid. The density increased markedly at temperatures in the range of 1500°-1600°C and remained constant thereafter. The formation of a eutectic liquid at 1550°C was attributed to the steep increase in density. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 8 publications
0
34
0
Order By: Relevance
“…Then, powders of TiH x and Al were mixed, pulverized and heated at 973 K for 1 h in Ar environment. By this procedure, fine powders of Al 3 Ti of several microns in diameter could be obtained.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, powders of TiH x and Al were mixed, pulverized and heated at 973 K for 1 h in Ar environment. By this procedure, fine powders of Al 3 Ti of several microns in diameter could be obtained.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…35) Such extreme processing conditions result in exaggerated grain growth of the sintered materials leading to degradation of mechanical properties. 57) In the previous work, we have reported that the addition of Al 3 Ti improves the sintering at 1273 K of TiB 2 powders. 8) It has been shown that TiB 2 and Al 3 Ti coexist stably at 1273 K and by the addition of Al 3 Ti up to 30 mass%, the Vickers hardness of the sintered materials increases up to as high as 2100 Hv.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most research involving the wear resistance of TiB 2 has focused on TiB 2 with appreciable amounts of binder phase or with TiB 2 as a reinforcement phase for a softer ceramic or alloy [126][127][128][129][130][131][132]. The presence of only a few percent porosity in monolithic TiB 2 has been shown to have a significant impact on erosion resistance.…”
Section: 2: Introductionmentioning
confidence: 99%
“…In order to obtain nearly fully dense material, sintering temperatures of 1800ºC or higher are usually needed unless large additions of sintering aids, especially metallic, are used [63][64][66][67][68][123][124][125]. Studies have shown that small additions of Si 3 N 4 or metallic elements such as Fe or Ni perform exceptionally well at reducing the temperatures and pressures required to sinter TiB 2 to near 100% density [102,126]. TiC and TiN additions are common in the sintering of TiB 2 , usually in high concentrations, because they aid in sintering while inhibiting grain growth due to their immiscibility in TiB 2 [63,65,85].…”
Section: 2: Introductionmentioning
confidence: 99%